Light in the Dark: Retrieving Underwater Irradiance in Shallow Eutrophic Waters From AC-S Measurements - Gonçalves-Araujo, Rafael; Markager, Stiig (Frontiers in Marine Science, 2020)
Light is essential for primary production and, therefore, its attenuation controls the vertical distribution of plants and phytoplankton over the water column. The diffuse attenuation of irradiance (K) is mainly governed by the attenuation by the water itself and the concentrations of optically active substances (e.g., phytoplankton, inorganic particles and colored dissolved molecules), which makes it an important parameter for eutrophication monitoring. Over the past century, Denmark has had recurrent eutrophication events, with extreme episodic cases where anoxic conditions were observed. Since the 1980’s, eutrophication in Danish waters has been monitored with regards to the diffuse attenuation coefficient of scalar irradiance (Ko) of photosynthetically active radiation (PAR, 400–700 nm), Ko(PAR). However, radiometric measurements in Denmark are difficult in winter due to low solar zenith angle and only few light hours. On top of that, radiometric measurements in the first meters of the water column are highly affected by light refraction influenced by waves, compromising the monitoring of shallow turbid waters as in Denmark. Therefore, we developed a semi-analytical model based on data to from a spectral AC instrument (AC-S, Sea-Bird Scientific) that can estimate the underwater light field and the diffuse attenuation coefficient of downwelling irradiance, Kd(PAR). We tested two distinct approaches based on equations from the literature for estimation of Kd(PAR). The results show that modelled PAR profiles follow the overall shape of in situ radiometric profiles but with smoother profiles, especially in the surface layer (2–5 m). Along with that, the method provided robust Kd(PAR) estimates, that were strongly correlated to the reference Ko(PAR) values from in situ profiles and with low root mean square error (RMSE). Thus, AC-S data can be used to estimate the underwater light field and Ko(PAR). This will make possible to retrieve Ko(PAR) in the absence of daylight and, therefore, allow for environmental monitoring outside the daylight hours, making environmental monitoring more efficient. In addition, the method provides valuable insights into the factors controlling light attenuation.